KONSEP WAKAF UANG - Chonita Lutfyah; DEWI VAHLEVI (STAI AN-NAJAH INDONESIA MANDIRI, 2022)
The word waqf (plural: awqaf) has the significance of detainment or anticipation. In more detail, that waqf implies something whose substance (unmistakable resources) is kept up with, and furthermore the advantages and results are worked in view of the desires of somebody who has submitted (waqif) with a lawful cycle in light of the waqf capability. Waqf as per Regulation Number 41 of 2004 is a lawful demonstration of wakif that isolates or surrenders part of the wakif's property to be utilized on a continuous premise or for a specific period following its inclinations for love or public government assistance as per the Shari'a. The Fatwa Commission of the Indonesian Ulema Committee has laid out a fatwa with respect to cash waqf which makes sense of that (1) cash waqf (cash waqf or waqf al-Nuqud) is waqf completed by an individual, gathering, foundation, or legitimate element as cash or money, ( 2) remembered for the meaning of cash are protections, (3) cash waqf is lawfully reasonable (jawaz), (4) cash waqf must be submitted and utilized for something allowed by syar'i, and (5) esteem the head of money waqf should be ensured for its supportability, it can't be sold, gave or acquired. Concerning the arrangements and specialized execution of money waqf in Unofficial law Number 42 of 2006 the Execution of Waqf, to be specific (1) Kinds of resources gave over by waqif in real money waqf are cash in rupiah money (2) Money waqf is helped out through Shariah Monetary Establishments selected by the Pastor of Religion as LKS-Beneficiary of Money Waqf (LKS-PWU). Keywords: Concept, Waqf, Cash References Ahmad Azhar Basyir, Hukum Islam Tentang Wakaf, Ijarah dan Syirkah, Bandung: PT. Al- Ma’arif, 1987. Al-Bakri, I’anatu Ath-Thalibin, Kairo: Isa Halabi, tt. Az-Zuhaili, Wahbah, Dr., Al-Fiqhu al-Islami wa ‘Adillatuhu, Damaskus: Dar al-Fikr, tt. Irfan Syauqi Beik, Wakaf Tunai dan Pengentasan Kemiskinan, ICMI online, Halal Guide, September 2006. M.A. Mannan, 2001, Sertifikat Wakaf Tunai Sebuah Inovasi Instrumen Keuangan Islam, Ciber, PKTTI-UI. Muhammad, Abu As-Su’ud, Risalatu fi Jawazi Waqfi AnNuqud, Beirut; Dar Ibn-Hazm, 1997 Syarif Hidayatullah. 2016 wakaf uang dalam perspektif hukum Islam dan hukum positif di Indonesia, jurnal SALAM: jurnal sosial dan budaya syar-I. vol.3 no.1. Syekh Muhammad Abid As-Sindi, Musnad Syafi’i, Sinar Baru Algensindo, Bandung. 2000.